Isolation and whole genome sequencing of a lipophilic anaerobic bacterium, a representative of the species complex Corynebacterium tuberculostearicum, from a tuberculosis focus - O. B. Ogarkov; A. E. Suzdalnitsky; I. G. Kondratov; Yu. S. Bukin; E. A. Orlova; V. V. Sinkov; S. N. Zhdanova; N. L. Belkova; L. V. Rychkova; L. I. Kolesnikova (Acta Biomedica Scientifica)
Background. The study of the lower respiratory tract microbiome has been actively developed inrecent years with the help of whole genome sequencing (WGS) methods. Due to this, it became clear that the nature of the lungs microbiota is very different from other microbial communities inhabiting the human body. One of the important directions in the study of pathological lungs biocenosis is the study of the role of the satellite microbiota of the tuberculosis focus. The aim of the work. To isolate and characterize oxygen-tolerant anaerobes from the necrotic contents of tuberculomas. Materials and methods. Biopsy material from 5 patients with pulmonary tuberculosis was obtained during a planned surgical treatment of tuberculoma. A pure culture was isolated from one sample during anaerobic cultivation. Lipase activity of strain was determined by plating on brain heart infusion agar (HIMEDIA, India) supplemented with 0.1 % Tween-80 and 10 mM of CaCl2. Antibiotic susceptibility was determined by RAPMYCO and SLOWMYCO of TREK Diagnostic Systems (Thermo Fisher Scientific, USA). DNA from the sediment of the broth culture was isolated by the CTAB chloroform method. Whole genome sequencing was performed on a DNBSeq-G400 NGS sequencer by Genomed (Russia). Results. Based on WGS results and phylogenetic analysis, the strain was identified as Corynebacterium kefirresidentii. The strain was characterized by high lipase activity and resistance only to Isoniazid, Ethionamide and Trimethoprim/Sulfamethoxazolin. Conclusion. The isolation of a lipophilic anaerobic representative of the Corynebacterium tuberculostearicum species complex from a tuberculous focus indicates a  possible role of the non-tuberculous microbiota in the liquefaction of caseous necrosis. We assumed that in some cases, favorable conditions are created inside the tuberculous focus for the development of satellite anaerobic lipophilic microbiota.